Impacts of agriculture on PM10 pollution and human health in the Lombardy region in Italy - Renna, Stefania; Lunghi, Jacopo; Granella, Francesco; Malpede, Maurizio; Di Simine, Damiano (Frontiers in Environmental Science, 2024)
Air pollution is one of the main environmental health concerns globally, with particulate matter (PM) as the primary threat. While many policies address emissions from transport and industry, there is growing evidence of agriculture's significant impact on air quality. Evaluating how intensive farming impacts PM concentrations and public health is necessary for informed policy interventions. We focus on the Po Valley (Italy), characterized by intensive agricultural practices and substantial pollution levels. Our study examines secondary inorganic aerosol (SIA) concentrations between 2013 and 2020 in Lombardy. Our findings reveal key insights into the impact of intensive farming on air pollution and public health. First, we find that ammonium salts make up over 30% of the daily particulate matter ≤ 10 µm (PM10), with annual levels [11.6-11.8 µg/m3] reaching half of the European Union's proposed limit (20 µg/m3). Second, exposure tends to peak in low-wind conditions. In Milan, ammonia predominantly flows from the east, aligning with heavy livestock activity, while nitrogen oxides' (NOx) impacts seem more localized. Rural SIA peaks correlate with winds from NOx-rich areas. These outcomes imply that targeted, single-sector policies might fall short of significantly reducing PM 10 concentrations. Additionally, manure spreading raises SIA levels by 2-3 µg/m3 in urban backgrounds the following days. Local sources also stand out in back-trajectory modeling of concentrations. Finally, applying long-term concentration-response functions to ammonium salts as a fraction of PM10, our study suggests that pollution stemming from agricultural activities in Milan leads to approximately 589 [446-866] deaths annually, resulting in an average loss of 6,951 [5,267-10,222] life years. This equates to 43 [33-64] deaths and 511 [387-751] lost life years for every 100,000 residents.